2021
DOI: 10.1111/jvim.16067
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac extracellular volume fraction in cats with preclinical hypertrophic cardiomyopathy

Abstract: Background: Cardiac magnetic resonance imaging (CMR) allows for detection of fibrosis in hypertrophic cardiomyopathy (HCM) by quantification of the extracellular volume fraction (ECV). Hypothesis/Objectives: To quantify native T1 mapping and ECV in cats. We hypothesize that native T1 mapping and ECV will be significantly increased in HCM cats compared with healthy cats. Animals: Seventeen healthy and 12 preclinical HCM, age-matched, client-owned cats. Methods: Prospective observational study. Tests performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“… 19 A more recent study that utilized gadolinium to calculate extracellular volume fraction, an indirect measure of myocardial fibrosis, showed that cats with HCM had an increase in this variable, presumably due to myocardial fibrosis. 20 This presumption was strengthened by the fact that this variable correlated well with echocardiographic measures of diastolic dysfunction.…”
Section: Pathophysiologymentioning
confidence: 99%
“… 19 A more recent study that utilized gadolinium to calculate extracellular volume fraction, an indirect measure of myocardial fibrosis, showed that cats with HCM had an increase in this variable, presumably due to myocardial fibrosis. 20 This presumption was strengthened by the fact that this variable correlated well with echocardiographic measures of diastolic dysfunction.…”
Section: Pathophysiologymentioning
confidence: 99%
“…It has been speculated in humans that LA dysfunction might reflect early myocardial fibrosis, 30,40 which could be a marker for early HCM 40 . A recent study showed that LAFS% in cats with subclinical HCM was correlated with LV extracellular volume, a measure of interstitial fibrosis, but not with LVWT 41 . Abnormal collagen metabolism has been also suggested in Ragdoll cats carrying MYBPC3 R820W mutation without LVH, 42 and interstitial fibrosis has been described on histopathology in cats diagnosed antemortem with mild subclinical HCM 43 .…”
Section: Discussionmentioning
confidence: 99%
“…40 A recent study showed that LAFS% in cats with subclinical HCM was correlated with LV extracellular volume, a measure of interstitial fibrosis, but not with LVWT. 41 Abnormal collagen metabolism has been also suggested in Ragdoll cats carrying MYBPC3 R820W mutation without LVH, 42 and interstitial fibrosis has been described on histopathology in cats diagnosed antemortem with mild subclinical HCM. 43 Thus, our findings of LA dysfunction might, as in humans, reflect abnormal myocardial properties that precede overt HCM.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly in cats, reduction in MAPSE is associated with a worse prognosis 6 and cats with HCM have a reduced GLS, suggesting reduced overall longitudinal systolic function. 11,28 In humans, displacement of the aortic root is used to assess longitudinal systolic function. This is referred to as systolic aortic root motion (SARM), aortic root systolic excursion (ARSE) and anterior aortic plane systolic excursion (AAPSE).…”
Section: Discussionmentioning
confidence: 99%